Homology of Ribosomal Ribonucleic Acid of Desulfovibrio Species with Desulfovibrio vulgaris - Pace, B. (1971)
Three species of Desulfovibrio were found to have a high degree of ribosomal ribonucleic acid homology with Desulfovibrio vulgaris. Desulfotomaculum nigrificans, which is also a sulfate-reducing anaerobe, had only 38% ribosomal ribonucleic acid homology with D. vulgaris. The homologies of six other unrelated genera were determined and found to be lower than 50%.